2012
DOI: 10.1149/2.057210jes
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Agent Optimization for Nonspecific Binding on Phage Based Magnetoelastic Biosensors

Abstract: Magnetoelastic biosensors have been studied for the past few years for use in detecting bacteria for food safety. These magnetoelastic biosensors are composed of a bio-molecular recognition element and transducer platform (magnetoelastic resonator). Phages (biomolecular recognition element) have been developed to provide very specific binding with Salmonella typhimurium bacteria. However, there is some binding (non-specific binding) of bacteria to the gold areas not covered with phage on both the measurement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…However, a BSA concentration of 10 mg/ml did not result in an increase in the number of MRSA bound on the measurement sensors. The higher concentration of BSA did not guarantee the maximum binding of MRSA, which was in agreement with a previously published result [22]. The reason of significantly lower binding of MRSA at 10 mg/ml of BSA concentration in both sensors is presumably associated with the shape and size of BSA.…”
Section: Optimization Of the Concentration Of Bsasupporting
confidence: 87%
See 2 more Smart Citations
“…However, a BSA concentration of 10 mg/ml did not result in an increase in the number of MRSA bound on the measurement sensors. The higher concentration of BSA did not guarantee the maximum binding of MRSA, which was in agreement with a previously published result [22]. The reason of significantly lower binding of MRSA at 10 mg/ml of BSA concentration in both sensors is presumably associated with the shape and size of BSA.…”
Section: Optimization Of the Concentration Of Bsasupporting
confidence: 87%
“…Therefore, open areas on the sensor (between phages) must be blocked with a blocking agent to prevent non-specific binding on the sensor. A previous study [22] showed that BSA has superior blocking ability when compared to casein and fat-free milk. Therefore, BSA was selected as a blocking agent and the different concentration of BSA was used in order to determine the optimum concentration of BSA (Fig.…”
Section: Optimization Of the Concentration Of Bsamentioning
confidence: 97%
See 1 more Smart Citation
“…However, the direct detection of ME biosensors without washing procedures was sometimes limited due to the non-specific bindings on the * Electrochemical Society Active Member z E-mail: parkmik@auburn.edu measurement and control sensors. Thus, Shen et al, 19 optimized the blocking condition by selecting a blocking agent and its concentration. However, fresh produce have diverse surface properties depending on surface hydrophobicity, surface constitutional characteristics, and surface morphology.…”
mentioning
confidence: 99%
“…The selection of the best extraction procedures solved the nonspecific binding on the sensor in a certain range; however, the extraction did not solve all possible nonspecific binding problems. The best blocking reagent needs to satisfy certain requirements, including blocking the space between the E2 phages and not interfering with the capacity of the E2 phage to interact with its target [23,24]. Since BSA, casein, and PEG have been popularly used as blocking reagents on plastic or gold surfaces [11,16,29], these reagents were selected for this study.…”
Section: Selection Of Blocking Reagentmentioning
confidence: 99%